2016
DOI: 10.1016/j.bjorl.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoscopy evaluation protocol for the differentiation of essential and dystonic voice tremor

Abstract: The protocol of specific tasks by means of transnasal fiberoptic laryngoscopy is a viable method to differentiate between essential and dystonic voice tremor syndromes through the following tasks: /s/ production, continuous whistling and reduction of tremor in falsetto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…This involvement does not distinguish vocal tremor of essential tremor from spasmodic dysphonia. A cross sectional study of 19 ear, nose, and throat patients with either essential tremor or dystonic tremor found that dystonic patients were more likely to have reduction of tremor in the palate (P=0.02), pharynx (P=0.038), and larynx (P=0.002) when using a higher “falsetto” pitch 36…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…This involvement does not distinguish vocal tremor of essential tremor from spasmodic dysphonia. A cross sectional study of 19 ear, nose, and throat patients with either essential tremor or dystonic tremor found that dystonic patients were more likely to have reduction of tremor in the palate (P=0.02), pharynx (P=0.038), and larynx (P=0.002) when using a higher “falsetto” pitch 36…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…No que se refere ao ano de publicação dos estudos, observaram-se pesquisas que datam do início dos anos 1990 (1993 e 1994), bem como pesquisas contemporâneas referentes aos anos de 2016 e 2017 A frequência de publicações sobre o tema é limitada, considerando-se que este estudo não realizou demarcações temporais na sua busca por artigos. Os anos que apresentaram mais trabalhos foram os de 1994 e 2016, com a publicação de dois estudos por ano (Borges, Ferraz, & Andrade, 1994;Moraes & Biase, 2016;Medeiros et al, 2016). A Tabela 1 apresenta a descrição dos artigos que foram incluídos e analisados nesta revisão, demonstrando seus títulos, autores e anos de publicação das pesquisas.…”
Section: Figura 2 Resultado Da Busca Nas Bases De Dadosunclassified
“…Na discussão sobre os temas mais analisados nos estudos, destacam-se as pesquisas referentes à caracterização clínica do TE. Nesse sentido, afirma-se que costuma acometer as mãos e os antebraços dos indivíduos, podendo ou não acometer ambas as mãos, manifestando-se também em outras partes do corpo, como a cabeça (Azevedo & Meyer, 2017;Zeigelboim & Mittelmann, 2008), e provocando alterações na emissão vocal em 11% a 30% dos casos (Moraes & de Biase, 2016). Observa-se ainda que a constância dos tremores varia entre 4Hz e 12Hz, tendo evolução lenta durante os anos e apresentando comorbidades associadas (Azevedo & Meyer, 2017).…”
Section: Discussionunclassified
“…Diagnoses were made by observing tremors that occurred during vowel production and during the tasks that separated the two types of action tremors, i.e., emission of the continuous /s/ and the whistle. Tremors were classified as essential when observed during the execution of both types of tasks and dystonic when not observed during the emission of /s/ and the whistle 5 , 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Dystonic vocal tremor is phonation dependent and does not occur in non-phonated emissions. These postures and specific tasks should be evaluated by nasofibrolaryngoscopy to classify and differentiate the types of vocal tremors 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%